EVALUATING THE EFFECTIVENESS OF NUTRITION EDUCATION FOR WIC SERVICE CLIENTS IN MANHATTAN - KANSAS - Al Bashabsheh, Zaher (My University, 2015)
In spite of the improvement of nutrition education and the realization of the importance of healthy dietary patterns, the prevalence of unhealthy dietary patterns is still increasing among vulnerable groups (e.g. women and children). Therefore, healthy nutrition education is needed to increase low income families knowledge about healthy food choices. The purpose of this study was to evaluate clients satisfaction of nutrition education methods (individual counseling, interactive notebooks, and online nutrition education) used by the Women, Infants, Children (WIC) program in Manhattan, Kansas, to educate pregnant women, postpartum women and caregivers for children. A cross-sectional survey of 100 clients was conducted using self-reported questionnaire. The WIC staff assigned clients with high risk to individual counseling, whereas clients with low risk assigned to interactive notebooks, online education, or individual counseling. The clients received two nutrition education sessions during the certification process. Nutrition education topics used for this study were whole grains, fruits and vegetables, breastfeeding, MyPlate, and infant feeding. The survey was distributed by the WIC staff and given to the clients after the second nutrition education session. One-way ANOVA and Tukey- Pairwise Comparisons test were performed to find which method has highest client satisfaction. Tukey- Pairwise test shows a significant difference between individual counseling and online method (P = 0.0149). Individual counseling had significantly higher client satisfaction scores than online nutrition education method. However, there is no significant difference between individual counseling and notebooks nutrition education. These findings indicate that clients who were assigned to use individual counseling method were more likely to be satisfied than clients who used notebooks and online nutrition education methods.
Keywords: WIC; Nutrition education; Healthy food choices; Public Health (0573)